Analisis Dan Perancangan Sistem Informasi Penggajian Karyawan Harian Pada PT. Sukaya Jambi - Fernanda, Fernanda; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
Currently PT. Sukaya Jambi is growing and developing in terms of providers of trade in goods and services, especially in Jambi province by utilizing the development of information technology. But not all developments in information systems technology are applied to PT. Sukaya jambi, so that problems arise in the salaries of employees at PT. This crocodile. The payroll process at PT. Sukaya is still using a simple computerized system using Microsoft Excel and notebooks as a tool so it takes a long time to get detailed payroll data. Therefore, the authors provide solutions in the form of daily employee payroll information systems using UML (Unified Modeling Language) modeling tools. This research produces a prototype that can be further implemented so as to produce a payroll information system that can support and assist the financial activities of PT. Sukaya Jambi and its employees.